2022
DOI: 10.3389/fneur.2022.893401
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Abdominal Visceral Fat Content and Plasma Adiponectin Level With Intracranial Atherosclerotic Stenosis: A Cross-Sectional Study

Abstract: BackgroundAbdominal obesity and adipocytokines are closely related to atherosclerosis, and adiponectin level is considered one of the important clinical indicators. This study aimed to analyze the associations of abdominal visceral fat content and adiponectin level with intracranial atherosclerotic stenosis (ICAS).MethodsA total of 186 patients were enrolled in this study. Patients were distributed into ICAS and non-ICAS by the degree of artery stenosis. Plasma adiponectin levels and the ratio of visceral adip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…Finally, 27 papers (18 cross-sectional and 9 cohort studies) published between 2010 and 2023, which met our inclusion criteria, were included. Amongst the included studies, six articles examined the association between VAT-to-SAT ratio and blood pressure (BP) [ 15 , 23 , 31 – 34 ], 9 studies examined atherosclerosis indices [ 24 , 35 42 ], 10 studies examined CVDs events [ 26 , 43 51 ] and remaining two studies assessed CVDs risk scores [ 25 , 52 ]. Among the reviewed studies, eleven were conducted in Japan [ 26 , 31 , 33 , 36 , 38 , 39 , 41 , 43 , 47 , 48 , 51 ], six in USA [ 15 , 40 , 42 , 44 , 49 , 52 ], three in Brazil [ 25 , 35 , 45 ], three in China [ 24 , 34 , 50 ], two in South Korea [ 23 , 32 ], one in Netherlands [ 37 ], and one in Portugal [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, 27 papers (18 cross-sectional and 9 cohort studies) published between 2010 and 2023, which met our inclusion criteria, were included. Amongst the included studies, six articles examined the association between VAT-to-SAT ratio and blood pressure (BP) [ 15 , 23 , 31 – 34 ], 9 studies examined atherosclerosis indices [ 24 , 35 42 ], 10 studies examined CVDs events [ 26 , 43 51 ] and remaining two studies assessed CVDs risk scores [ 25 , 52 ]. Among the reviewed studies, eleven were conducted in Japan [ 26 , 31 , 33 , 36 , 38 , 39 , 41 , 43 , 47 , 48 , 51 ], six in USA [ 15 , 40 , 42 , 44 , 49 , 52 ], three in Brazil [ 25 , 35 , 45 ], three in China [ 24 , 34 , 50 ], two in South Korea [ 23 , 32 ], one in Netherlands [ 37 ], and one in Portugal [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Bogorodskaya et al [ 42 ] suggested that there is a correlation between VAT-to-SAT ratio and CAC score > 0 (OR = 3.57, p < 0.001) in CVD-free patients with human immunodeficiency virus (HIV) as well as an increased risk of the presence of atherosclerotic plaques (OR = 3.30, p = 0.03). According to the study conducted by Wang et al [ 24 ], the VAT-to-SAT ratio was proposed as an independent predictor for intracranial atherosclerosis (ICAS) (OR = 26.08; 95% confidence interval (CI): 5.92–114.83; p < 0.001) in a sample of 186 patients with an average age of 67.19 ± 8.68. Higuchi et al [ 39 ] conducted a cross-sectional study on 3007 healthy Japanese adults.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Decreased plasma adiponectin levels are associated with an increased risk of intima-media thickness ( 145 ) and intracranial AS stenosis ( 146 ). Gasbarrino et al analyzed plasma adiponectin in patients with severe carotid AS undergoing carotid endarterectomy ( 147 ).…”
Section: Protective Adipokines For Asmentioning
confidence: 99%